IMPLEMENTASI DISCOVERY LEARNING UNTUK MENGAJARKAN MAHIR MENULIS TEKS DESKRIPSI - NANI RAHMAWATI (JURNAL ILMIAH KOHESI, 2021)
The purpose of this research is to teach students proficient in writing description text. Students can better understand andunderstand more quickly in the process of imprisonment, and be more courageous to give their own opinions. This isdirected at the responses and responses of students in writing a description text based on their own experience anddeveloping it into a description paper. With this research will help teachers in the use of discovery learning in learning to writedescription text. The use of discovery learning methods is expected to achieve the learning objectives of the material writingthe description text.